Sort your career out & make more money - Johnson, Shelley; James, Glen (John Wiley & Sons Australia, Ltd, 2023)
The best investment you can make is in yourself and your career Sort Your Career Out: And Make More Money is your go-to guide for building a career that you love. Dream jobs don't just come along: you need to make them happen. And this is the book that will show you how, from creating the ultimate career strategy to getting paid what you're really worth. (Hint: It's not just about changing the font on your resume!) With tips and guidance from two of today's top money and career experts, you'll learn how to change jobs, secure a promotion, ask for a pay rise and much, much more. Whether you're preparing for a job interview or you're looking to make a radical change, Sort Your Career Out has the smart advice you need for earning more and winning at work. Inside you'll find practical activities that will help boost your bankability and take you further, faster. Along the way, you'll also follow diverse case studies from real employees: people who have been there, done that, and figured out the way forward. Sort Your Career Out: And Make More Money unpacks everything you need to: Establish your career mindset: define your purpose and unlock your skills and strengths Set concrete goals and create new opportunities for yourself Upskill with essential tips and templates for resumes, cover letters, interviews, networking, and more Know when to take risks and how to handle setbacks like burnout and unemployment It's time to discover more career flexibility and achieve your long-term goals. With this must-read handbook, you'll be ready to move up, move on, and feel more fulfilled with what you do every day.